2022
DOI: 10.1021/acsnano.2c10209
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Room Temperature Ferromagnetism in Highly Strained 2D Semiconductor Cr2Ge2Te6

Abstract: Emergent magnetism in van der Waals materials offers exciting opportunities in fabricating atomically thin spintronic devices. One pertinent obstacle has been the low transition temperatures (T c) inherent to these materials, precluding room temperature applications. Here, we show that large structural gradients found in highly strained nanoscale wrinkles in Cr2Ge2Te6 (CGT) lead to significant increases of T c. Magnetic force microscopy was utilized in characterizing multiple strained CGT nanostructures leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Strain should also be considered as one of the mechanisms to induce edge magnetization. It was shown that strain can enhance magnetism in CGT. , It is plausible that some strain appears at low temperatures at the interface between the amorphous and crystalline CGT regions. The last mechanism that we can consider is related to the in-plane dangling bond.…”
Section: Discussionmentioning
confidence: 99%
“…Strain should also be considered as one of the mechanisms to induce edge magnetization. It was shown that strain can enhance magnetism in CGT. , It is plausible that some strain appears at low temperatures at the interface between the amorphous and crystalline CGT regions. The last mechanism that we can consider is related to the in-plane dangling bond.…”
Section: Discussionmentioning
confidence: 99%
“…192 Notably, Adam O'Neill et al experimentally detected the strain-induced increment of T C in Cr 2 Ge 2 Te 6 utilizing MFM combined with the ab initio and DFT studies (Figure 21e,f). 175 The wrinkles were created by mechanically bending a flexible substrate coated with Cr 2 Ge 2 Te 6 (Figure 21g). It was calculated that the T C of 1L Cr 2 Ge 2 Te 6 could elevate from ∼50 K to ∼150 K with 5% strain, while the T C of the bilayer could increase close to room temperature with 5% strain (Figure 21f).…”
Section: Extrinsic 2d Ferromagnets/antiferromagnetsmentioning
confidence: 99%
“…2D ferromagnets coupled with their electronic and optical properties, could facilitate advanced magnetic, ,, magnetoelectric, and magneto–optical applications. Flexibility and facile modulation of ferromagnetic/antiferromagnetic properties by local or external perturbations, such as strain, interlayer interactions, and electric field modulation, are well-known advantages of 2D ferromagnets.…”
Section: D Ferromagnets/antiferromagnetsmentioning
confidence: 99%
See 2 more Smart Citations